Differences Training Method Dynamic and Static Stretching Effectiveness on Flexibility of Torso and Hip Joints on students in SD N 1 Samplangan Gianyar Year 2012 - Kamasuta, I Made Arya (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
One of the components of biomotoric for a person is flexibility. Flexibility is the ability to perform the motion in the joint space. Increased flexibility can be obtained by practice. One form of exercise that can be used to increase flexibility is stretching exercises. This type of stretching exercises that can increase the flexibility of the training methods of dynamic stretching and static stretching training methods. This study aims to determine the effectiveness of the differences between the methods of dynamic stretching and static stretching method flexibility of the torso and of the hip joint in elementary students. This research uses quasi-experimental research design rather nonequivalent control group design. Sample consisted of 36 people chosen by total sampling, the sample was divided into two groups by randomized: group training dynamic stretching and static stretching training group. The data was collected by measuring the flexibility of the torso and the hip joint before and after administration of each treatment group with a sit and reach test. The results of this study is on dynamic stretching of the training group increased an average flexibility of the torso and hip joint at 4,422 cm while in the static stretching training group increased an average flexibility of the torso and hip joint at 7,044 cm. Independent T test based on this difference was statistically significant with a significance level of p=0.000 means that there are differences between the methods of training effectiveness of dynamic stretching and static stretching training methods to the flexibility of the torso and hip joint. Based on the above findings suggested the sports teacher to use static stretching training in an effort to increase the flexibility of the torso and hip joint.
Keywords: Dynamic stretching, static stretching, flexibility